2010
DOI: 10.1109/led.2009.2035934
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fringe Capacitance on the Performance of Nanoscale FinFETs

Abstract: In this letter, we report the enhanced fringe capacitance in FinFETs when compared to the equivalent planar MOSFETs at the 22-nm node. We show that this increase is due to the 3-D nature of the device and also due to the close proximity of the source/drain (S/D) epitaxial (epi) region to the metal gate. Using well-calibrated 3-D mixed-mode simulations, we show that this will cause the performance of FinFETs to be significantly degraded, unless proper device optimizations are carried out. Our results also indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 9 publications
(8 reference statements)
1
13
0
Order By: Relevance
“…UTB-SOI MOSFETs have a higher access resistance than FinFETs, a major fraction of which is from the contact resistance due to the lower contact area [27]. On the other hand, FinFETs have a higher outer fringe capacitance compared to UTB-SOI MOSFETs due to the 3D nature of the device [28]. By reducing the fin pitch to 80 nm, it is possible to reduce the outer fringe capacitance and make it equal to that of UTB-SOI MOSFET device.…”
Section: Comparison Between Technologiesmentioning
confidence: 99%
“…UTB-SOI MOSFETs have a higher access resistance than FinFETs, a major fraction of which is from the contact resistance due to the lower contact area [27]. On the other hand, FinFETs have a higher outer fringe capacitance compared to UTB-SOI MOSFETs due to the 3D nature of the device [28]. By reducing the fin pitch to 80 nm, it is possible to reduce the outer fringe capacitance and make it equal to that of UTB-SOI MOSFET device.…”
Section: Comparison Between Technologiesmentioning
confidence: 99%
“…Advantages of FinFETs over conventional planar MOSFETs are high immunity to short-channel effects, drain-induced barrier lowering, high gate controllability, and reduction of leakage current [2][3][4]. Although FinFETs are potentially advantageous for further scaling, parasitic components present an important obstacle: fringing capacitances increase with scaling due to the increasing proximity of the source/drain selective epitaxial growth (SEG) region [5] and of the massive contact with a short length of interconnect to the gate [6], and series resistance also increases as the width of the fins is narrowed [7,8]. These parasitics degrade circuit-level performance metrics such as digital circuit delay and analog/RF performance [6].…”
Section: Introductionmentioning
confidence: 99%
“…The essential idea behind these MOSFET structures is to allow the gate electrode to have better control of the electric potential of the MOSFET channel such that both a high turn-on driving current and an extremely low tum-off leakage current may be obtained. When used for high-frequency applications however, these MOSFET structures may exhibit serious shortcomings due to the associated parasitic capacitances and resistances [2]. Recent research works in the literature have reported high performance MOSFET structures of nanometre scale.…”
Section: Introductionmentioning
confidence: 99%